Intestinal permeability in human cardiovascular diseases: a systematic review and meta-analysis - Xiao, Jiang-Hong; Wang, Yu; Zhang, Xi-Mei; Wang, Wen-Xiao; Zhang, Qiao; Tang, Yu-Ping; Yue, Shi-Jun (Frontiers in Nutrition, 2024)
Background: There is a link between cardiovascular diseases and intestinal permeability, but it is not clear. This review aimed to elucidate intestinal permeability in cardiovascular diseases by metaanalysis.Methods: Multidisciplinary electronic databases were searched from the database creation to April 2023. All included studies were assessed for risk of bias according to the Joanna Briggs Institute Critical Appraisal Checklist. The heterogeneity of each study was estimated using the I 2 statistic, and the data were analyzed using Review Manager 5.3 and Stata 16.0. Results: In total, studies in 13 pieces of literature were included in the quantitative meta-analysis.These studies were conducted among 1321 subjects mostly older than 48. Patients had higher levels of intestinal permeability markers (lipopolysaccharide, d-lactate, zonulin, serum diamine oxidase, lipopolysaccharide-binding protein, intestinal fatty acid binding protein, and melibiose/rhamnose) than controls (standard mean difference SMD = 1.50; 95% CI = 1.31-1.88; P < 0.00001). Similarly, lipopolysaccharide levels were higher in patients than in controls (SMD = 1.61; 95% CI = 1.02-2.21; P < 0.00001); d-lactate levels were higher in patients than in controls (SMD = 1.16; 95% CI = 0.23-2.08; P = 0.01); zonulin levels were higher in patients than in controls (SMD = 1.74; 95% CI = 1.45-2.03; P < 0.00001); serum diamine oxidase levels were higher in patients than in controls (SMD = 2.51; 95% CI = 0.29-4.73; P = 0.03).The results of the meta-analysis verified that the intestinal barrier was damaged and intestinal permeability was increased in patients with cardiovascular diseases. These markers may become a means of the diagnosis and treatment of cardiovascular diseases.